Oral malodour among adolescents and its association with health behaviour and oral health status. Issue 2 (22nd June 2015) - Rani, H; Ueno, M; Zaitsu, T; Kawaguchi, Y
Abstract: Objective: To assess oral malodour level and its association with health behaviour, oral health behaviour and oral health status among adolescents. Method: A questionnaire survey and clinical examination that included tongue coating and oral malodour status were conducted on 665 senior high school students in Saitama, Japan. Analyses of Pearson chi‐square, independent samples t ‐test and logistic regression were conducted using SPSS 19.0 with the significance level set at P < 0.05. Results: There were 173 (26.0%) subjects who had oral malodour and 54.7% of subjects reported they were conscious of their own oral malodour. Logistic regression analysis showed that subjects who skipped breakfast were 1.7 times more likely to have oral malodour than those who had breakfast. Subjects who did not have the habit of cleaning their tongue daily were also 1.7 times more likely to have oral malodour compared to those who had the habit. The odds of having oral malodour increased as the area of tongue coating widened. Conclusion: Tongue coating, daily tongue cleaning and breakfast are significant factors for oral malodour among adolescents. Proper tongue coating management together with other healthy lifestyle behaviours, especially having breakfast, should be advocated in adolescents' health education.